Quality Characteristics and Antioxidant Potential of Lemon (Citrus limon Burm. f.) Seed Oil Extracted by Different Methods - Park, Yong-Sung; Kim, Il-doo; Dhungana, Sanjeev Kumar; Park, Eun-Jung; Park, Jae-Jung; Kim, Jeong-Ho; Shin, Dong-Hyun (Frontiers in Nutrition, 2021)
Lemon (Citrus limon Burm. f.) is one of the most widely produced and consumed fruits in the world. The seeds of lemon are generally discarded as waste. The purpose of this study was to investigate the quality characteristics and antioxidant potential of lemon seed oil obtained by four extraction methods (roasted-pressing at 170°C, RP-170; roasted-pressing at 100°C, RP-100; cold-pressing, CP; and supercritical fluid, SF). No significant differences in the viscosity, density, and refractive index were observed in the oil obtained from different methods. In the case of Hunter’s value, L (lightness) and b (yellowness) values of SF were higher than those of the others. The oil obtained by the CP method exhibited higher levels of Ca (252.17 mg/kg), Cu (2.38 mg/kg), K (225.98 mg/kg), and Mog (0.4769.88 mg/kg) than that of other methods. The highest contents of total phenols (165.90 mg/mL) and flavonoids (21.69 mg/mL) were significantly high in oil obtained by the SF method. Oleic and linoleic acids consisted of principal fatty acids, which were significantly higher in oil obtained by RP-170. Higher amounts of volatile flavor compounds, such as γ-terpinene, sabinene, and limonene, were observed in CP compared to those observed for the other methods. This study elucidates the effects of different methods of oil extraction on the composition of lemon seed oil and highlights potential applications of these benefits in the food, cosmetic, pharmaceutical, and/or fragrance industries.